Development of highly efficient technological medium-power multi-frequency gyrotrons for plasma applications based on magnetically-shielded solenoids - Proyavin, M. D; Manuilov, V. N; Morozkin, M. V; Sobolev, D. I; Glyavin, M. Yu (SPIE, 2020)
Due to a growing interest for microwave radiation sources with a radiation frequency of several tens of GHz and output power of several tens of kW, we developed a new generation of technological gyrotron setups. The key feature of these systems is a novel magnetic system based on magnetically shielded solenoids (MSS). This magnetic system is several times more energy efficient than the common warm solenoids and it also allows to control the properties of the helical electron beam to make it interact with various cavity modes. The developed MSS provides a high field induction in the interaction space and a small stray field, so the gyrotron can operate in wide range of magnetic fields (from 1 T to 1.8 T in relatively low-consumption regime). It allows a gyrotron complex to operate within a wide frequency range (from 24 to 50 GHz on main cyclotron resonance). A total system efficiency expected to be about 35%, which is significantly higher than the existing analogs.